2009
DOI: 10.1016/j.nedt.2009.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Towards a team-based, collaborative approach to embedding e-learning within undergraduate nursing programmes

Abstract: SummaryE-learning approaches are incorporated in many undergraduate nursing programmes but there is evidence to suggest that these are often piecemeal and have little impact on the wider, nurse education curriculum. This is consistent with a broader view of e-learning within the higher education (HE) sector, which suggests that higher education institutions (HEIs) are struggling to make e-learning a part of their mainstream delivery (HEFCE, 2005). This article discusses some of the challenges that face contemp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 62 publications
0
10
0
4
Order By: Relevance
“…The range of IT support for tertiary learning, including within nursing curricula is steadily increasing (Maag, 2004;Maag, 2005;. Given student satisfaction with the integration of technologies such as digital recordings into tertiary learning and teaching environments locally and internationally (Cooke, et al, 2012;Kiteley and Ormrod, 2009;Lu et al, 2009) it seems unlikely that even the most negative reports of impact on academic performance will see them removed from university offerings. Mildly negative impacts of IT supports such as those reported in this study merely direct academic staff to consider supplementing IT course-enhancements like digital recordings with ongoing support to ensure that they are most effectively used by student populations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The range of IT support for tertiary learning, including within nursing curricula is steadily increasing (Maag, 2004;Maag, 2005;. Given student satisfaction with the integration of technologies such as digital recordings into tertiary learning and teaching environments locally and internationally (Cooke, et al, 2012;Kiteley and Ormrod, 2009;Lu et al, 2009) it seems unlikely that even the most negative reports of impact on academic performance will see them removed from university offerings. Mildly negative impacts of IT supports such as those reported in this study merely direct academic staff to consider supplementing IT course-enhancements like digital recordings with ongoing support to ensure that they are most effectively used by student populations.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that students feel online activities enhance their learning, give them tools to practice learning and allow them to study at their own pace (Koch et al, 2010). However, students still appear to largely prefer face-toface lectures, but consider it optimal if online lectures supplement, rather than replace, the traditional mode of contact teaching (Cooke et al, 2012;Kiteley and Ormrod, 2009;Salamonson and Lantz, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…•Özellikle çalışan öğrenciler için eğitim zamanını ailesi, işi gibi sorumlulukları göz önüne alarak istedikleri zamana göre seçmelerine olanak tanıması (Horiuchi, Yaju, Koyo and Sakyo 2009;Kala, Isaramalai and Pohthong 2010;Kiteley and Omrod 2009).…”
Section: Web Tabanlı Uzaktan Eğitimin Avantaj Ve Dezavantajlarıunclassified